2023
DOI: 10.1177/0976500x231175220
|View full text |Cite
|
Sign up to set email alerts
|

Selective Partial Agonism of Vasopressin 1a Receptors In Vitro by OCE-205

Abstract: Objective To test the selectivity and degree of functional agonism of Ocelot Bio’s dual agonist/antagonist molecule, OCE-205, at the vasopressin 1a receptor (V1aR). Methods Cells expressing human (h) or rat V1a, V1b, V2, or oxytocin receptors (OTR) were incubated with varying concentrations of OCE-205 or with arginine vasopressin (AVP), and responses were measured with fluorescence or reporter gene assays. In addition, human resistance arteries were exposed to increasing concentrations of OCE-205, and the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Studies in human blood vessels have demonstrated in vitro V1a selective activity and behavior akin to a partial agonist. 35 Generating data on portal blood flow is much more challenging to accomplish in rodent models. Only two phenomena reduce PP: either splanchnic vasoconstriction restricts flow, or a change in hepatic resistance allows the same flow at decreased pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies in human blood vessels have demonstrated in vitro V1a selective activity and behavior akin to a partial agonist. 35 Generating data on portal blood flow is much more challenging to accomplish in rodent models. Only two phenomena reduce PP: either splanchnic vasoconstriction restricts flow, or a change in hepatic resistance allows the same flow at decreased pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based functional assays of OCE-205 support both its function as an effective partial agonist and its selectivity for the V1a receptor, with no activity at the human or rat V2 receptor at therapeutic concentrations. 35 In healthy animals, this partial agonist mechanism was demonstrated, with a plateau effect achieving submaximal increases in MAP that were driven by similar increases in SBP and DBP (Bukofzer et al, "OCE-205 in Rats and Non-Human Primates: Pharmacokinetic and Pharmacodynamic Analysis", submitted manuscript).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Binding of the agonist domain to V1a receptors drives the desired vasoconstrictive effect, while binding of the antagonist domain in a competitive manner would prevent maximal activation of the V1a receptor pool. Cell-based functional assays of OCE-205 provide support for this partial agonism, with no activity at the human or rat V2 receptor ( Croston et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…OCE-205 is a novel peptide designed to target the vasopressin receptor system as a mixed agonist/antagonist for the V1a receptor, resulting in effective partial agonism. The activity at human V1a receptors plateaus at ∼50% maximum possible effect (EC 50 for human V1a = 0.70 nM), with little to no activity at human V2 receptors at clinically relevant concentrations ( Croston et al, 2023 ). Thus, unlike other AVP analogs, OCE-205 should not cause water retention due to V2 activation and should result in the desired vasoconstrictive effect for treating complications related to cirrhotic PHT (e.g., HRS-AKI), with fewer unwanted effects, by modulating disease pathophysiology.…”
Section: Introductionmentioning
confidence: 99%